70.2k views
3 votes
X - y = 1
Convert the equation from standard form to slope-intercept form.​

2 Answers

4 votes

Answer:

y=x-1

Explanation:

It is y=x-1 because first when we do ANYTHING first. We leave the y on the left side of the equation, since the slope y=mx+b has the y always on the left side. So we subtract x from both sides and we get -y=-x+1. We are NOT DONE yet, so after this, we divide both sides by -1. Why? This is because you cannot have a negative y. Dividing both sides by -1 you finally get y=x-1. If this is trouble some to read, I will also put how to solve the problem down below. :)

Let's solve for y.

x−y=1

Step 1: Add -x to both sides.

x−y=1+−x

−x

−y=−x+1

Step 2: Divide both sides by -1.

−y/ −1 = −x+1 /−1

y=x−1

Answer:

y=x−1

User Andrew Samuelsen
by
4.0k points
4 votes

Answer:

y=x-1

Explanation:

The equation is currently in standard form which is a+b=y and slope-intercept is y=mx+b where m is the slope and b is the y-intercept. To change the form we must move the terms around using Properties of Equality.

First, subtract 1 from both sides

x-y-1=1-1

x-y-1=0

Then, add y to both sides

x-y-1+y=0+y

x-1=y

So that is the equation in slope-intercept form with a slope of 1 and a y-intercept of -1.

User Yoram De Langen
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.